2001
DOI: 10.1523/jneurosci.21-03-00983.2001
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Morphological and Functional Organization of the Hippocampus in a p35 Mutant Model of Cortical Dysplasia Associated with Spontaneous Seizures

Abstract: Cortical dysplasia is a major cause of intractable epilepsy in children. However, the precise mechanisms linking cortical malformations to epileptogenesis remain elusive. The neuronalspecific activator of cyclin-dependent kinase 5, p35, has been recognized as a key factor in proper neuronal migration in the neocortex. Deletion of p35 leads to severe neocortical lamination defects associated with sporadic lethality and seizures. Here we demonstrate that p35-deficient mice also exhibit dysplasia/ heterotopia of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 97 publications
2
76
1
1
Order By: Relevance
“…Consistent with these reports, our results suggest that mossy fibers in LIS1 mutants exhibit relatively normal axonal projections toward area CA3. Moreover, we did not find evidence for polysynaptic responses to afferent stimulations or the types of epileptiform burst discharges that accompany recurrent mossy fiber circuits in any mature or newborn granule cell as reported for acquired epilepsy models (Wuarin and Dudek, 2001;Hunt et al, 2009Hunt et al, , 2010 or other models of neuronal migration disorder (Wenzel et al, 2001;Patel et al, 2004;Kwon et al, 2006;Patrylo and Willingham, 2007). Therefore, mossy fiber sprouting does not appear to be a contributing factor to the pathology of LIS1 haploinsufficiency, despite significant granule cell displacement, hyperexcitability, and spontaneous seizures in LIS1 mutant mice.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Consistent with these reports, our results suggest that mossy fibers in LIS1 mutants exhibit relatively normal axonal projections toward area CA3. Moreover, we did not find evidence for polysynaptic responses to afferent stimulations or the types of epileptiform burst discharges that accompany recurrent mossy fiber circuits in any mature or newborn granule cell as reported for acquired epilepsy models (Wuarin and Dudek, 2001;Hunt et al, 2009Hunt et al, , 2010 or other models of neuronal migration disorder (Wenzel et al, 2001;Patel et al, 2004;Kwon et al, 2006;Patrylo and Willingham, 2007). Therefore, mossy fiber sprouting does not appear to be a contributing factor to the pathology of LIS1 haploinsufficiency, despite significant granule cell displacement, hyperexcitability, and spontaneous seizures in LIS1 mutant mice.…”
Section: Discussioncontrasting
confidence: 56%
“…The convergence of these features in a mouse model could have significant consequences for circuit information processing and/or contribute to the generation of pathological network excitability associated with type I lissencephaly. A number of genetically based animal models of MCD have been developed, and most show robust hyperexcitability and/or spontaneous seizures (Wenzel et al, 2001;Kellinghaus et al 2004;Patel et al, 2004;Kwon et al, 2006;Harrington et al, 2007;Patrylo and Willingham, 2007;Nosten-Bertrand et al, 2008;Greenwood et al, 2009;Kerjan et al, 2009). When synaptic mechanisms have been investigated, these studies have typically reported postsynaptic alterations in glutamatergic excitatory Auerbach et al, 2011;Bateup et al, 2011;Luikart et al, 2011) or GABAergic inhibitory currents (Trotter et al, 2006;Ackman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, although these animal models often have structural malformations characteristic of human migration disorders, they rarely present with spontaneous, recurrent seizures. An exception is the p35 knock-out mouse, which exhibits both structural malformations and spontaneous seizures (Chae et al, 1997;Wenzel et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cdk5 knock-out mice display severe cortical lamination defects but die in the early perinatal period (Ohshima et al, 1996;Gilmore et al, 1998;Tanaka et al, 2001). In contrast, whereas the p35 knock-out mouse also demonstrates cortical lamination defects, it suffers from only sporadic adult lethality and exhibits spontaneous limbic-like seizures (Tsai et al, 1994;Ohshima et al, 1996;Gilmore et al, 1998;Tanaka et al, 2001;Wenzel et al, 2001;Gupta et al, 2003). Many brain regions of p35Ϫ/Ϫ animals exhibit structural abnormalities (Chae et al, 1997;Kwon and Tsai, 1998;Kwon et al, 1999).…”
Section: Introductionmentioning
confidence: 99%